Integrated staged tests of football players at advanced specialization stage - Berdnikova, A. N.; Hosseini Hezri, A.; Zakharova, A. V.; Kondratovich, S. V. (Theory and Practice of Physical Culture, 2018)
The study analyses design and content of the integrated staged tests of football players in the advanced specialization stage including physical, technical and mental fitness tests. The study gives the hemodynamic test rates; functionality test rates generated by a gas-analyzer system; and the mental fitness test rates of the 12-13 year-old football players, with a special emphasis on the technical skills and physical fitness. The study data and analyses showed the physical fitness rates of the sample being within the age norm. Junior football players at the prime specialization stage are normally tested with high speed-strength and endurance rates. The still low maximal oxygen consumption rates of the 12-13 year olds (52.1±7.4 ml/kg/min) may be explained by the inadequate anaerobic capacities, low maximum ventilation (MV) rates (80.4±18.7 l/min), and, to a lesser extent, by the still low leg strength. The technical skills tests made it possible to identify the key problems including the low accuracy of the passes and shots on goal. The junior football players were tested with high response and response stability rates; with 28% tested prone to emotional imbalances; 14% tested with fair emotional control skills; and most of the sample tested driven by emotions and game situations i.e. their behaviour was found the temperament- and age-specific. The study data and analyses were applied to produce recommendations on how the education and training process may be improved.